2021
DOI: 10.1007/s00204-021-03132-x
|View full text |Cite
|
Sign up to set email alerts
|

The diarrhetic shellfish-poisoning toxin, okadaic acid, provokes gastropathy, dysbiosis and susceptibility to bacterial infection in a non-rodent bioassay, Galleria mellonella

Abstract: Diarrhetic shellfish-poisoning (DSP) toxins such as okadaic acid and dinophysistoxins harm the human gastrointestinal tract, and therefore, their levels are regulated to an upper limit of 160 μg per kg tissue to protect consumers. Rodents are used routinely for risk assessment and studies concerning mechanisms of toxicity, but there is a general move toward reducing and replacing vertebrates for these bioassays. We have adopted insect larvae of the wax moth Galleria mellonella as a surrogate toxicology model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Interestingly, at higher temperature (25 °C), there was a similar response with pupation as it was faster with larvae exposed to a higher dose of radiation and likely due to a response to environmental stressors as seen with silkworms exposed to non-ionising (ultraviolet) radiation (Nojima et al 2019). Incidentally, G. mellonella fed an altered diet also triggered early pupation (Emery et al 2021; reviewed by Zhang et al, 2019) and this was observed in other insects exposed to environmental stressors such as house fly (exposed to ozone; Levy et al, 1972) and butterfly species (exposed to haze smoke; Tan et al, 2018) – though those stressors have other significant impacts on the survivability and development of those insect models, including smaller pupae and emergent adults. Interestingly, it is the faecal load produced by G. mellonella exposed to ionising radiation that produced a significant effect.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, at higher temperature (25 °C), there was a similar response with pupation as it was faster with larvae exposed to a higher dose of radiation and likely due to a response to environmental stressors as seen with silkworms exposed to non-ionising (ultraviolet) radiation (Nojima et al 2019). Incidentally, G. mellonella fed an altered diet also triggered early pupation (Emery et al 2021; reviewed by Zhang et al, 2019) and this was observed in other insects exposed to environmental stressors such as house fly (exposed to ozone; Levy et al, 1972) and butterfly species (exposed to haze smoke; Tan et al, 2018) – though those stressors have other significant impacts on the survivability and development of those insect models, including smaller pupae and emergent adults. Interestingly, it is the faecal load produced by G. mellonella exposed to ionising radiation that produced a significant effect.…”
Section: Discussionmentioning
confidence: 98%
“…This effect of environmental stress leading to increased faecal pellet production can also be observed in Mongolian gerbils (Barone et al, 1990; Okano et al, 2005). It will not be surprising if the nature of viable bacteria varies under ionising radiation as it is known that stress (be it psychological, physical and environmental) alters the gut microbiota (Karl et al, 2018; Emery et al, 2021). For example, ozone (O 3 ) and nitrogen dioxide (NO 2 ) as air pollutants alter the human gut microbiome (Fouladi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possible association agrees with the alterations in the pattern of expression of 10 genes related to carcinogenic processes in SH-SY5Y neuronal cells exposed to OA [ 182 ]. Poisoning with toxins from the OA group at sub-regulatory levels could have long-term adverse effects on the digestive tract in people, leading to an increased risk of bacteriosis, likely from an existing resident gut symbiont or pathobiont [ 199 , 200 ]. The disruption of epithelial integrity by OA may affect the colonic microbiota, which, in turn, leads to various diseases such as colorectal cancer [ 201 ].…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%
“…OKA is a polyether fatty acid extracted from marine sponges, and it has been widely used to study the propagation of neurotoxicity of different animal models. OKA selectively inhibits protein phosphatases PP1 and PP2A. Inhibition of PP2A, in particular, combined with triggered activation of several major phosphorylating pathways, including MAPK and ERK, induce the hyperphosphorylation of the tau protein, thereby giving rise to the tau aggregates.…”
Section: Introductionmentioning
confidence: 99%